Learning Mathematics: One Minute - Amir Zuhairi Zakaria; Haslina Hassan; Hanasrullah Halim; Wan Amirah Najwa Wan Idris; Muhammad Asyraf Abdullah Zawawi; Nur Fathihah Mansor (International Journal of Multimedia and Recent Innovation, 2020)
This game is made with purpose to educate student in terms of mathematical skill combined with fun adventure game. The target audience is the students should be primary-school (10-13 years old). This is an educational game and made on purpose to create a difference method to present solving a mathematical problem to the audience. The user will play a game where the character is chased by a dog and must avoid obstacles such as river. In each level of the game, the user must find a door in which they must solve the mathematical question as pass code. Successful in solving the mathematical question will bring user to another level. This game is made with 3 level and must be completed within 1 minute. This game can be used as a tool for learning. The level of mathematical questions is simple mathematical quiz, designed with objective to teach early age students.